PERCEPTION OF FAMALE PLASTIC SURGEONS ON THE PROCESS OF MEDICAL TRAINING AND THE INFLUENCE ON THE FEMALE BODY - Mendes, Ana Clara Barboza; Moraes, Marília Teixeira de; Almeida, Rogério José de (Revista Gênero e Interdisciplinaridade, 2026)
The female body has a defined aesthetic standard disseminated by social media. And the characteristics established as ideal are unattainable without cosmetic plastic surgery, which implies extremely high numbers of these procedures. The patient is mostly female and, paradoxically, the surgeon who shapes (female) aesthetics is predominantly male. This study aimed to understand the perception of female plastic surgeons regarding the female body and cosmetic plastic surgery. This is a descriptive cross-sectional study with a qualitative and exploratory approach. Semi-structured interviews were conducted with female plastic surgeons who performed cosmetic plastic surgery. In total, seven interviewees participated in the research, a number that allowed for theoretical saturation. After conducting, transcribing, and analyzing the interviews, with subsequent coding of the interviewees’ statements, the following explanatory categories of the phenomenon emerged: 1) training up to plastic surgery; 2) perception of the female body; 3) perception regarding patients’ choices; 4) responsibility of plastic surgery in establishing social body standards. It was possible to verify that the career paths of these female doctors were marked by various situations of gender discrimination. And that women are still not the majority in surgical specialties. The reasons why patients seek gender-based plastic surgery stem from the false idea that men possess greater capabilities; from contexts of jealousy on the part of their partners; or from the feeling that female surgeons value their patients’ complaints more. Women seek an unattainable and hypersexualized beauty standard. The media plays a crucial role in fueling this often unfair and even abusive desire. This incites an unchecked increase in the demand for cosmetic plastic surgery, trivializing these procedures, ignoring their enormous scope, and disregarding their risks.